Understanding DSM-5 Hoarding Disorder: A Triple Vulnerability Model. Issue 2 (2nd April 2016) - Raines, Amanda M.; Oglesby, Mary E.; Allan, Nicholas P.; Short, Nicole A.; Schmidt, Norman B.
Abstract : Objective : Whereas a triple vulnerability model has been used to evaluate several anxiety- and mood-related conditions, no research has purposefully examined hoarding from this perspective. Method : Using a multivariate approach, the current study evaluated the unique relations between hoarding and a general biological (e.g., neuroticism), psychological (e.g., anxiety sensitivity), and hoarding-specific vulnerability (e.g., saving cognitions) within 526 individuals. Results : A structural equation model (SEM) including all three vulnerabilities as well as hoarding symptoms provided good fit to the data. Consistent with the model, the vulnerabilities accounted for a substantial percentage (66%) of the variance in hoarding severity. Conclusions : These findings suggest that, similar to other emotional distress disorders, risk for hoarding can be conveyed through a constellation of general and specific vulnerabilities. Future research should continue to examine this model, particularly utilizing a prospective design and clinical sample.